(untitled) (Proceedings of Faculty of Civil Engineering, 2025)
This paper analyses the thermal effects in composite beams using an analytical solution for a two-layer beam across three types of models: fully composite (no slip between layers), partially composite (limited slip) and non-composite beams (free slip). Laminated glass is selected as a representative example of a composite beam. The applicability and accuracy of the analytical solution are verified by a comparison to experimental results from the literature, taking into account that rising temperatures cause gradual softening of the interlayer in laminated glass.